(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2021)
Soil acts as a large reservoir of Organic Carbon (OC) but the amount varies significantly with space and time. Thus, soil analysis and interpretation of spatial variability of Soil Organic Carbon (SOC) are keys to site-specific management. The study aimed to characterize the spatial variability of SOC in an active floodplain. Soil samples were collected in three major landform categories (natural levee, back slope, marsh land) from the lower Brahmaputra River floodplain and then analyzed for SOC measurement in the laboratory. The measured data were then analyzed for spatial variability interpretation using descriptive statistics and geo-statistical analysis. The study found that the amount of SOC varies with landform variation, soil texture and distance between sample points. The topsoil of marsh land has the highest (1.41%), back slope holds a moderate amount (1.15%) and the natural levee has the lowest (0.75%) amount of SOC. The amount of clay particles at the top layer was found to be positively correlated to the SOC whereas in the same layer of sand and silt showed a negative correlation. The geo-statistical analysis illustrated the nugget effect. Low (<1%) SOC is commonly found in the agricultural soils of Bangladesh which was corroborated in this study; moderate (1.1%) SOC was found in the floodplain. This study aimed to provide an insight into spatial variability to assist in predicting SOC in the active floodplain; consequently, the interpretation of spatial variability analysis can be implemented for site specific management strategies and to calculate carbon stock in floodplain soils. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 8(2), 2019, P 33-40